The watchmaker's hand [large type] - Deaver, Jeffery (Deaver, Jeffery. Lincoln Rhyme novel, 2023)
"When a New York City construction crane mysteriously collapses, causing mass destruction and injury, Rhyme and Sachs are on the case. A political group claims responsibility for the sabotage and threatens another attack in twenty-four hours, unless its demands are met. Then a clue reveals to Rhyme that his nemesis, known as the Watchmaker, has come to town to fulfill his promise of murdering the criminalist. With New York in a panic, Rhyme and his team must unravel a handful of plots as tightly wound as a timepiece--before more cranes falls, raining down death and destruction from above"--